2014
DOI: 10.3174/ajnr.a3986
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Lymphoproliferative Disorders (OLPDs): Value of MR Imaging for Differentiating Orbital Lymphoma from Benign OPLDs

Abstract: BACKGROUND AND PURPOSE: Accurate discrimination of orbital lymphoma from benign orbital lymphoproliferative disorders is crucial for treatment planning. We evaluated MR imaging including DWI and contrast-enhanced MR imaging for differentiating orbital lymphoma from benign orbital lymphoproliferative disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
80
3
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(99 citation statements)
references
References 23 publications
12
80
3
1
Order By: Relevance
“…Diffusion-weighted imaging (DWI) allows quantification of the diffusion properties of water molecules (4), and its derived apparent diffusion coefficient (ADC) map is widely accepted as a useful tool to detect and characterize orbital lesions (56789). Generally, due to the enlarged nuclei, hyper-cellularity, and subsequent limited extra-cellular space, malignant orbital tumors demonstrate lower ADC value than the benign tumors (5678910). However, the reproducibility of ADC measurements is still a challenge during clinical practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diffusion-weighted imaging (DWI) allows quantification of the diffusion properties of water molecules (4), and its derived apparent diffusion coefficient (ADC) map is widely accepted as a useful tool to detect and characterize orbital lesions (56789). Generally, due to the enlarged nuclei, hyper-cellularity, and subsequent limited extra-cellular space, malignant orbital tumors demonstrate lower ADC value than the benign tumors (5678910). However, the reproducibility of ADC measurements is still a challenge during clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…However, the reproducibility of ADC measurements is still a challenge during clinical practice. Previous study has shown that ADC value can be affected by several factors, such as the magnetic field strength, MRI acquisition parameters, and also the region of interest (ROI) selection methods (10). …”
Section: Introductionmentioning
confidence: 99%
“…Preoperative differentiation of orbital lymphoma and orbital inflammation is highly clinically relevant since treatment strategies vary substantially. Low‐dose radiation therapy is considered the first‐line treatment for orbital lymphoma, whereas patients with orbital inflammation undergo corticosteroid therapy …”
mentioning
confidence: 99%
“…In addition, standard magnetic resonance imaging (MRI) cannot permit the differentiation of orbital lymphoma and orbital inflammation, because they both appear as isointense or hypointense on T 1 ‐ and T 2 ‐weighted images. Moreover, both of them show moderate enhancement after injection of gadolinium‐based MR contrast agents . Haradome et al suggested that orbital inflammation often presented "flow void sign," but the characteristics of standard MRI are not reliable.…”
mentioning
confidence: 99%
“…The lower ADC is thought to reflect higher cellularity in orbital lymphoma. 20 Infections, such as orbital cellulitis, can be difficult to discriminate from IOP; however, a search for adjacent sinus disease, particularly within the ethmoid sinus, and early abscess formation would facilitate the diagnosis. In cases where IOP has a more diffused and infiltrative morphology, the diagnosis may be more challenging;…”
Section: Idiopathic Orbital Pseudotumormentioning
confidence: 99%